Economic impacts of alternative kidney transplant immunosuppression: A national cohort study. Issue 4 (11th March 2020) - Axelrod, David A.; Caliskan, Yasar; Schnitzler, Mark A.; Xiao, Huiling; Dharnidharka, Vikas R.; Segev, Dorry L.; McAdams‐DeMarco, Mara; Brennan, Daniel C.; Randall, Henry; Alhamad, Tarek; Kasiske, Bertram L.; Hess, Gregory; et al.
Abstract: Understanding the economic implications of induction and maintenance immunosuppression (ISx) is important in developing personalized kidney transplant (KTx) care. Using data from a novel integrated data set including financial records from the University Health System Consortium, Medicare, and pharmacy claims (2007‐2014), we estimated the differences in the impact of induction and maintenance ISx regimens on transplant hospitalization costs and Medicare payments from KTx to 3 years. Use of thymoglobulin (TMG) significantly increased transplant hospitalization costs ($12 006; P  = .02), compared with alemtuzumab and basiliximab. TMG resulted in lower Medicare payments in posttransplant years 1 (−$2058; P  = .05) and 2 (−$1784; P  = .048). Patients on steroid‐sparing ISx incurred relatively lower total Medicare spending (−$10 880; P  = .01) compared with patients on triple therapy (tacrolimus, antimetabolite, and steroids). MPA/AZA‐sparing, mammalian target of rapamycin inhibitors‐based, and cyclosporine‐based maintenance ISx regimens were associated with significantly higher payments. Alternative ISx regimens were associated with different KTx hospitalization costs and longer‐term payments. Future studies of clinical efficacy should also consider cost impacts to define the economic effectiveness of alternative ISx regimens.